Landraces of forage maize as source of genetic variability for organic farming - Monteagudo A.B.; Campo L.; Salleres B.; Moreno J. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Concern for the preservation of the environment is a constant at present. The European Commi - ssion has developed specific directives to prevent pollution and degradation of the environment. In agriculture, organic farming is presented as an alternative to intensive agriculture that is more polluting and straining on natural resources. Most of the maize breeding materials currently commercialized are not adapted to organic farming conditions and the gene pool has been shrinking after years of genetic selection. Therefore, the landraces used in breeding programs could introduce new genes to obtain materials adapted to new agriculture systems. The aim of this work was to evaluate forage maize hybrids developed at Centro de Investigaciones Agrarias de Mabegondo (CIAM) under Organic Farming. These hybrids were obtained by crossing different Galician landraces with an inbred line which has Galician landrace background. These hybrids have shown good levels of genetic diversity of all studied traits. They were more vigorous and earlier than commercial ones. They had variability of fiber and lignin content but similar digestibility of in vitro organic matter, thus breeding programs could discern and exploit these traits. Therefore, landraces could provide new genes to current breeding programs in order to obtain materials more suited to new agricultural conditions.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)